A Case Study of Vocabulary Learning through Technology-Mediated Task-Based Language Teaching: Insights from Teachers and Students (Lembaga Pengembangan Kinerja Dosen, 2025)
Abstract : This qualitative case study examines teacher and student perspectives on Technology-Mediated Task-Based Language Teaching (TMTBLT) using Wordwall for English vocabulary learning in junior high school. Participants included one English teacher and six seventh-grade students. Data were collected through semi-structured interviews and analyzed thematically. Both teacher and students view this approach positively to the application of TMTBLT. The teacher found the approach enabled flexible, contextual task design and collaborative learning despite limited digital device access. Students showed high engagement, describing their learning experience as enjoyable and motivating while successfully applying newly acquired vocabulary in real-life communication. The findings demonstrate TMTBLT's effectiveness in improving vocabulary mastery and creating meaningful learning experiences.